Verpleegadministrasie in gesondheidsdienste - A. Viljoen (AOSIS, 1984)
Nursing administration, as a sub-system of health administration, is excercised within an environment characterised by a number of conflicts. The nurse leader can cope with these conflicts through prevention, solution or conflict regulation. Administrative leadership brings a new dimension to nursing administration which must be taken into account. It makes specific demands regarding the selection, training, development and utilisation of the nurse administrator. The author comes to the conclusion that the quality of nurse leaders is high and that they make an indispensable contribution to health services. For an even more meaningful contribution the author advises the institution of structured policy advisory teams in hospitals, joint post-graduate training of doctors and nurses for health administration and, from time to time, freeing nurses to other selected occupations to develop better understanding.